Reader in comedy an anthology of theory and criticism - Romanska, Magda; Ackerman, Alan (Bloomsbury Methuen Drama, 2017)
This unique anthology presents a selection of over seventy of the most important historical essays on comedy, ranging from antiquity to the present, divided into historical periods and arranged chronologically. Across its span it traces the development of comic theory, highlighting the relationships between comedy, politics, economics, philosophy, religion, and other arts and genres. Students of literature and theatre will find this collection an invaluable and accessible guide to writing from Plato and Aristotle through to the twenty-first century, in which special attention has been paid to writings since the start of the twentieth century. 0'Reader in Comedy' is arranged in five sections, each featuring an introduction providing concise and informed historical and theoretical frameworks for the texts from the period: * Antiquity and the Middle Ages * The Renaissance * Restoration to Romanticism * The Industrial Age * The Twentieth and Early Twenty-First Centuries. Among the many authors included are: Plato, Aristotle, Horace, Donatus, Dante Alighieri, Erasmus, Trissino, Sir Thomas Elyot, Thomas Wilson, Sir Philip Sidney, Ben Jonson, Battista Guarini, Moliere, William Congreve, John Dryden, Henry Fielding, Samuel Johnson, Oliver Goldsmith, Jean Paul Richter, William Hazlitt, Charles Lamb, Soren Kierkegaard, Charles Baudelaire, Bernard Shaw, Mark Twain, Henri Bergson, Constance Rourke, Northrop Frye, Jacques Derrida, Mikhail Bakhtin, Georges Bataille, Simon Critchley and Michael North. As the selection demonstrates, from Plato and Aristotle to Henri Bergson and Sigmund Freud, comedy has attracted the attention of serious thinkers. Bringing together diverse theories of comedy from across the ages, the Reader reveals that, far from being peripheral, comedy speaks to the most pragmatic aspects of human life.